Environmental Pollution: Assessing the Criminal Liability of Corporations - Hariman Satria (Faculty of Law, Hasanuddin University, 2018)
The Supreme Court sentenced PT Dongwoo Enviromental Indonesia (PT DEI) for disposing of hazardous and toxic wastes polluting the environment. Meanwhile, PT Adei Plantation & Industry (PT API) was charged with crime for the destruction of land damaging the environment. The research method used is normative legal research, which focuses on two approaches: case approach and conceptual approach. The results show that, first, PT DEI and PT API are charged criminally represented by the board as functioneel daderschap or directing mind and will. Second, PT DEI is charged with subsidized charges, while PT API is charged to alternative charges. Third, PT DEI and PT API are said to have committed a criminal act because management either the directors or regular employees commits a criminal offense for and on behalf of the corporation or in favor of the corporation. Fourth, to prove a corporation fault is through the aggregation of management mistakes or controlling personnel or regular employees in the corporation structure. Fifth, the principal penalty imposed on PT DEI is a fine of Rp 1.500,000,000. Similarly, PT API is fined Rp 650.000.000. Sixth; PT DEI is charged to additional crime in the form of deprivation of profits and closure of the company while PT API is an improvement due to crime. Seventh, with the closing of the company, the judges did not order the executors to liquidate the assets of PT DEI. Eighth, the imposition of the company's closing sanctions should take into account the impacts, such as the termination of employee relation and the interests of shareholders.